IMPLEMENTASI PROYEK ASEAN DALAM MENGHADAPI TANTANGAN INFORMATION & COMMUNICATION TECHNOLOGY (ICT) MASTERPLAN 2015 - Maghfira Tri Maulani; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The ASEAN ICT Masterplan 2015 (AIM 2015) has come a long way and completed by the end of 2015. Since its launch in 2011, the AIM 2015 has provided a framework and roadmap for the development of information and communication technology (ICT) at the regional level and, as a result, has enabled greater ICT development in ASEAN. Over the past five years, ICT in ASEAN has improved in many respects. At the macro level, exports of ICT services have become a larger component of total service exports, suggesting that ICT is today an important engine of economic growth in the region. At the individual level, costs of internet access and mobile subscription have fallen sharply in ASEAN Member States (AMS), allowing greater connectivity for millions of ASEAN citizens. The advancement of ICT in ASEAN is also evident in other aspects; these include the rise in employment in the ICT sector, the transformation of government services into digital ones, and the increased awareness of cyber security, to name a few. Although many factors also played a contributing role in such developments, the AIM 2015 has been a vital instrument in bringing about efforts and endeavours of the AMS. The AIM 2015 supported the vision of AMS by bringing about many of the actions that account significantly for the region’s advancement. Without a doubt, the progress in the fields of ICT would not have come this far without the AIM 2015. Course, to achieve the success of ASEAN ICT MASTERPLAN 2015 through the various opportunities and challenges that are passable.Keywords : ICT, ASEAN, Masterplan 2015, Technology, Globalisation*Mahasiswa